2017
DOI: 10.1007/s00270-017-1622-4
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and 90Y-Radioembolization: Relation to Liver Function and Overall Survival

Abstract: Expected changes in pro- and anti-inflammatory cytokines after RE were shown. Furthermore, baseline values of IL-6 and IL-8 were associated with later liver dysfunction and survival. We hypothesize that these biomarkers are potential prognosticators and might help in patient selection for RE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 28 publications
4
27
0
Order By: Relevance
“…Both Fernandez-Ros et al and Seidensticker et al showed that proinflammatory cytokines were increased after Y90 treatment, the latter also suggested that high levels of IL-8 or IL-6 pre-treatment could predict decreased overall survival. 52,53 In summary, results from a number of studies suggest that locoregional therapies cause changes in tumourspecific and innate immune responses. It is very plausible that changes in the local cytokine and/ or chemokine milieu, which are difficult to measure in patients, result from locoregional therapies and affect not only effector cell responses, but also immune suppressor mechanisms such as MDSCs.…”
Section: Key Pointsmentioning
confidence: 99%
“…Both Fernandez-Ros et al and Seidensticker et al showed that proinflammatory cytokines were increased after Y90 treatment, the latter also suggested that high levels of IL-8 or IL-6 pre-treatment could predict decreased overall survival. 52,53 In summary, results from a number of studies suggest that locoregional therapies cause changes in tumourspecific and innate immune responses. It is very plausible that changes in the local cytokine and/ or chemokine milieu, which are difficult to measure in patients, result from locoregional therapies and affect not only effector cell responses, but also immune suppressor mechanisms such as MDSCs.…”
Section: Key Pointsmentioning
confidence: 99%
“…Due to a minimally embolic effect in comparison with PVE, radio-induced damage and cell death within the treated liver lobe are likely to be the main inducer of the hypertrophy in the contralateral RL after RE. Thus, we hypothesized that RL hypertrophy could be at least in part in relation to the levels of injuries and induction of cell death in the injected healthy liver and/or of the tumor itself possibly in relation to the production of growth factors and cytokines [ 17 20 ]. It is mandatory to keep in mind that the threshold doses inducing damages are different in tumor versus healthy liver.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CHE is considered to be an excellent marker in liver cirrhosis [12] and may therefore be crucial for pre-therapeutic evaluations of liver function especially in primary liver tumor patients and underlying liver cirrhosis. Up to date, only few studies take CHE levels into consideration, namely either as an inclusion criterion (baseline CHE levels within normal limits) [3] or for monitoring liver function after RE [36].…”
Section: Discussionmentioning
confidence: 99%